2020
DOI: 10.3941/jrcr.v14i12.4110
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Plasmacytoma of the breast in a patient with Multiple Myeloma

Abstract: Extramedullary plasmacytoma of the breast is rare. It is important to recognize the imaging findings and include it as a differential consideration in multiple myeloma patients with a breast mass. A 74-year-old woman undergoing chemotherapy for relapsed multiple myeloma presented with a palpable mass in her right breast. A screening mammogram four months prior was unremarkable. She underwent a diagnostic right mammogram which showed two well-circumscribed hyperdense masses. An ultrasound of the right breast sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Variable T1 and T2 signal intensities have been reported, including low-to-isointense signal on T1-weighted images and intermediate-to-high signal on T2-weighted images (Figure 8 24 ). 25,27 Restricted diffusion and homogenous enhancement with delayed washout kinetics have also been noted (Figure 8 24 ). [25][26][27] A limited number of studies have reported on 18 F-FDG PET/CT findings in breast plasmacytoma.…”
Section: Plasmacytomamentioning
confidence: 89%
See 1 more Smart Citation
“…Variable T1 and T2 signal intensities have been reported, including low-to-isointense signal on T1-weighted images and intermediate-to-high signal on T2-weighted images (Figure 8 24 ). 25,27 Restricted diffusion and homogenous enhancement with delayed washout kinetics have also been noted (Figure 8 24 ). [25][26][27] A limited number of studies have reported on 18 F-FDG PET/CT findings in breast plasmacytoma.…”
Section: Plasmacytomamentioning
confidence: 89%
“…25,27 Restricted diffusion and homogenous enhancement with delayed washout kinetics have also been noted (Figure 8 24 ). [25][26][27] A limited number of studies have reported on 18 F-FDG PET/CT findings in breast plasmacytoma. [26][27][28][29] Majority of these cases showed 18 F-FDG avidity, 26,27,29 although low-grade uptake has also been reported.…”
Section: Plasmacytomamentioning
confidence: 89%
“…Extramedullary soft tissue masses have been reported in the gingiva, liver, pituitary gland, small intestine, breast, thyroid cartilage, heart, testis, stomach, and soft tissue of the neck [5][6][7][8][9][10][11][12][13] . Soft-tissue involvement is associated with signi cantly shorter progression-free survival and overall survival, with a median survival of 8.5 months [14] .…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, BP accounted for roughly 1.5% of all plasmacytomas; of which, only 15% of these instances were classified as primary BP. The remaining 85% of cases were secondary to MM [ 6 , 11 ]. Through this case, we hope to provide insight into the diagnosis, treatment, and prognosis of this rare and intriguing type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that extramedullary plasmacytomas (EP) are often seen in patients with MM; however, these lesions are not necessarily solitary and widespread. Te symptoms associated with widespread proliferation of abnormal plasma cells are often greater, compared to symptoms seen due to a single lesion [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%